Actualizing lean construction: Barriers toward the implementation - Mohammad Asri, Mohammad Azwanie Naim; Mohd Nawi, Mohd Nasrun (AENSI Journals, 2015)
Lean thinking has been regarded as a success strategy in mass production, realizing cost and time saving while simultaneously improving competitive position in the market.It also can be interpret as a philosophy based on the concept of lean manufacturing.It is about managing and improving the construction process to profitably deliver what the customer need. Despite all the benefits that can be gained by implementing the idea of lean construction, all industry player need to consider the barriers obstructing its application.Through a review of a literature there are numbers of barrier that can be identified. The barriers toward the implementation are discussed in this paper.